Recombinant human follicle-stimulating hormone produces more oocytes with a lower total dose per cycle in assisted reproductive technologies compared with highly purified human menopausal gonadotrophin: a meta-analysis - Ezcurra Diego; Schertz Joan C; Lehert Philippe (BMC, 2010)
Abstract Background Human menopausal gonadotrophins and recombinant human follicle stimulating hormone are the two main gonadotrophin products utilized for controlled ovarian stimulation in assisted reproductive technologies. In this meta-analysis, the number of oocytes was designated as the most relevant endpoint directly resulting from ovarian stimulation, and therefore where the drug effect may be estimated with the best sensitivity. Methods All published randomized controlled trials on ovarian stimulation comparing the two gonadotrophin products were evaluated. Internal validity was determined using Chalmers' validated scale. If trials did not meet the established quality criteria, a sensitivity analysis assessed the stability of the results. The comparison of continuous variables was conducted following the weighted mean difference and the standardized mean difference (Cohen's effect size) with the random model. Given the known relationship of baseline conditions on treatment endpoints, results were adjusted for age, body mass index and type of infertility. Results Sixteen studies involving 4040 patients were included. Treatment with human menopausal gonadotrophins resulted in fewer oocytes (-1.54; 95% CI: -2.53 to -0.56; P < 0.0001) compared to recombinant human follicle-stimulating hormone. When adjusting for baseline conditions, the mean difference estimate was -2.10 (95% CI: -2.83 to -1.36; P < 0.001). A higher total dose of human menopausal gonadotrophin was necessary (mean difference, 235.46 IU [95% CI: 16.62 to 454.30; P = 0.03]; standardized mean difference, 0.33 [95% CI: 0.08 to 0.58; P = 0.01]). The pregnancy absolute risk difference (RD [hMG-r-hFSH]) for fresh transfers was 3% (P = 0.051), and the relative risk 1.10 (P = 0.06). When adjusted for baseline conditions, the relative risk was 1.04 (P = 0.49) and absolute difference was 0.01 (P = 0.34), respectively. Conclusions Because baseline conditions are predictive of outcome, meta-analytic results are more sensitive when these variables are considered. Using an endpoint closely associated with the stimulation period, sufficient sensitivity is achieved to compare gonadotrophin treatments. As the largest meta-analysis published to date on this subject, treatment with human menopausal gonadotrophins is characterized by fewer oocytes and a higher total dose. When considering only fresh transfers, pregnancy rates were similar.